Body mass index trajectories in pediatric multiple sclerosis. (5th April 2019) - Brenton, J Nicholas; Woolbright, Emma; Briscoe‐Abath, Christina; Qureshi, Asma; Conaway, Mark; Goldman, Myla D
Abstract : Aim: To characterize growth trajectories of children who develop multiple sclerosis compared to typically developing, regional peers and Centers for Disease Control (CDC) normative values. Method: This case–control study collected weight, height, and body mass index (BMI) in 40 consecutive pediatric patients with multiple sclerosis (28 females, 12 males), in addition to 120 typically developing peers (84 females, 36 males), identified and matched for year of birth, sex, ethnicity, and socio‐economic status. BMI values were converted to z‐scores based on CDC reference values and were compared with respect to age between our two cohorts and by years relative to multiple sclerosis onset for cases. Results: Median age for the clinical onset of multiple sclerosis was 15 years. BMI z‐scores are significantly higher for patients with multiple sclerosis compared to typically developing, demographically‐matched peers and CDC standards. These significant differences in BMI are noted from 4 years of age and onward. Height trajectories were similar among case and control individuals and CDC normative values. Interpretation: BMI in pediatric multiple sclerosis is markedly higher, beginning in early childhood, years before the clinical‐onset of the disease. What this paper adds: Children with multiple sclerosis are significantly more overweight than typically developing peers at the time of diagnosis. Body mass index trajectories are significantly higher years before the clinical manifestation(s) of multiple sclerosis. What this paper adds: Children with multiple sclerosis are significantly more overweight than typically developing peers at the time of diagnosis. Body mass index trajectories are significantly higher years before the clinical manifestation(s) of multiple sclerosis. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Gianfrancesco and Briggs on page 1243 of this issue. Resumen: Trayectorias del índice de masa corporal en esclerosis múltiple pediátrica: Objetivo: Caracterizar las trayectorias de crecimiento de los niños que desarrollan esclerosis múltiple en comparación con los valores normativos de desarrollo típico, los pares regionales y los Centros para el Control de Enfermedades (CDC). Método: Este estudio de casos y controles recopiló el peso, la estatura y el índice de masa corporal (IMC) en 40 pacientes pediátricos consecutivos con esclerosis múltiple (28 mujeres, 12 varones), además de 120 compañeros con desarrollo típico (84 mujeres, 36 varones), identificados y emparejados por año de nacimiento, sexo, etnia y estatus socioeconómico. Los valores de IMC se convirtieron en puntuaciones z basándose en los valores de referencia de los CDC y se compararon con respecto a la edad entre nuestras dos cohortes y por años en relación con el inicio de esclerosis múltiple para los casos. Resultados: La edad media para el inicio clínico de la esclerosis múltiple fue de 15 años. Las puntuaciones z de IMC son significativamente más altas para los pacientes con esclerosis múltiple en comparación con los pares con desarrollo demográfico y estándares CDC. Estas diferencias significativas en el IMC se observan a partir de los 4 años de edad. Las trayectorias de altura fueron similares entre los individuos de casos y controles y los valores normativos de los CDC. Interpretación: El IMC en la esclerosis múltiple pediátrica es notablemente más alto, comenzando en la primera infancia, años antes del inicio clínico de la enfermedad. Abstract : Trajetórias do índice de massa corporal em esclerose múltipla pediátrica: Objetivo: Caracterizar as trajetórias de crescimento de crianças que desenvolvem esclerose múltipla comparadas com pares regionais que se desenvolvem tipicamente e valores normativos do Centro para Controle de Doenças (CDC). Método: Este estudo de caso‐controle coletou peso, altura e índice de massa corporal (IMC) em 40 pacientes pediátricos consecutivos com esclerose múltipla (28 do sexo feminino, 12 do sexo masculino), além de 120 pares com desenvolvimento típico (84 do sexo feminino, 36 do sexo masculino), pareados para ano de nascimento, sexo, etnia, e nível sócio‐econômico. Os valores de IMC foram convertidos para escores z com base nos valores de referência do CDC e comparados com relação à idade entre as duas coortes, e por anos com relação ao início da esclerose múltipla para os casos. Resultados: A idade mediana para o início clínico da esclerose múltipla foi 15 anos. Os escores z do IMC foram significativamente mais altos para os pacientes com esclerose múltipla comparados aos pares com desenvolvimento típico e demograficamente pareados, e aos padrões do CDC. Estas diferenças significativas no IMC são notadas a partir dos 4 anos de idade. As trajetórias de altura foram similares entre casos, controles e valores normativos do CDC. Interpretação: O IMC em esclerose múltipla pediátrica é marcadamente mais alto, iniciando cedo na infância, anos antes do início clínico da doença.